Resilience among Elderly Widows in Lombok, Indonesia: A Case Study on Coping with Spousal Loss - Isatan Rodiah; Syamsul Hadi; Herlina Fitriana; Hidayahtus Sabrina (UIN Sulthan Thaha Saifuddin Jambi, 2025)
Becoming widowed in old age is a major challenge for women, often accompanied by grief, financial vulnerability, and social marginalization. However, many widows demonstrate resilience, namely the capacity to adapt and even grow when facing adversity. This study explores resilience among elderly widows in Lombok, Indonesia, within the cultural framework of the Sasak community. Using a qualitative case study design, data were collected from three participants through in-depth interviews, observation, and documentation, then analyzed with Miles and Huberman’s interactive model. The findings reveal that resilience develops through four interrelated stages: succumbing, survival, recovery, and thriving. Initially, participants experienced deep sorrow, but gradually adapted by reorganizing routines, relying on religious practices, and strengthening family and community ties. In some cases, this adaptation extended to the thriving stage, where widows discovered new meaning and contributed actively to their families and society. This resilience was supported by internal factors—such as spirituality, optimism, self-efficacy, and emotional regulation—as well as external support, including family, community networks, cultural norms, and health services. The study enriches resilience theory by confirming a staged and ecological model, while also accounting for specific cultural pathways shaped by spirituality and collectivist traditions. Practically, the findings underscore the importance of culturally grounded interventions, integrating spiritual practices, family support, and community care into counseling and social welfare programs for widows. Thus, adaptation to spousal loss is not only a psychological process, but also a culturally embedded pathway of recovery and growth.